Barriers to Care and Root Cause Analysis of LGBTQ+ Patients' Experiences: A Qualitative Study. Issue 6 (November 2021) - Nair, Julie McCulloh; Waad, Alex; Byam, Stacey; Maher, Madeline
Abstract : Background: LGBTQ+ (lesbian, gay, bisexual, transgender, queer/questioning, and others) people face a unique set of barriers to receiving quality healthcare. Very little exists in nursing literature that addresses these barriers. Objective: This study aimed to analyze patient experience data to better understand the context of barriers to care that LGBTQ+ patients experience, in addition to institutional responses. Methods: Documentary analysis was employed to review four LGBTQ+ patient experiences that resulted in formal feedback provided to the Office of Patient Relations. Each case was analyzed for content, process, and outcomes. Results: Through the outlined analysis, the study team found three primary themes and five secondary themes across the four cases. The overarching themes identified through the study's case review include (a) lack of provider knowledge, (b) lack of patient-centered care, and (c) lack of institutional infrastructures associated with the provision of affirming care to LGBTQ+ individuals. Discussion: Findings suggest the need for a multipronged approach when addressing the care of LGBTQ+ communities. A combination of provider-level education and institutional capacity building to treat diverse patient populations is necessary for addressing the issues demonstrated within the data. Moreover, further research is needed to identify unique needs of transgender and nonbinary patients and determine efficacy of institutional efforts to build capacity for caring and studying the health needs of LGBTQ+ communities.